y = sin( 4 x ) cos( 3 x )(adsbygoogle = window.adsbygoogle || []).push({});

f(x) = sin4x

g(x) = cos3x

f'(x) = cos4x

g'(x) = -sin3x

And by using the product rule, i'll get:

cos4x(cos3x) - sin4x(sin3x)

Is the answer correct or can be simplify again??

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Derivative of trigonometric functions

**Physics Forums | Science Articles, Homework Help, Discussion**